Sanksi Pidana terhadap Pelaku Pemalsuan Uang Ditinjau dari Hukum Positif dan Hukum Pidana Islam: Studi Putusan Nomor 1266/Pid.B/2023/Pn Mdn - Pratama, Muhammad Noval; Dintara Lubis, Syaddan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The crime of counterfeiting money is a formal crime, namely a crime that is considered to have been committed if a prohibited act has been carried out. In the criminal law system, the crime of counterfeiting currency is a very serious crime because the criminal threat for the perpetrators of this crime is an average maximum of 10 years in prison and a maximum fine of 10 billion rupiah, this provision has been regulated in Law No. 7 of 2011 concerning currency. This study aims to explain the criminal sanctions against perpetrators of counterfeiting money as reviewed from positive law and Islamic criminal law (Study of Decision Number 1266 / Pid.B / 2023 / Pn Mdn). The research method used can be classified as a type of qualitative research with a research procedure that will produce descriptive data in the form of written data from document data, laws and articles that can be reviewed. From the research that has been conducted, the results of the analysis of Islamic criminal law on the decision of the Medan District Court Number 1266/Pid.B/2023/Pn.Mdn regarding the crime of distributing counterfeit currency is a crime related to assets that can be subject to ta'zir sanctions. The determination of the imposition of ta'zir sanctions given by the judge is based on the level of crime committed by the defendant as the perpetrator directly committing the crime.